-5x-6(2x-2)=-107

Simple and best practice solution for -5x-6(2x-2)=-107 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-6(2x-2)=-107 equation:


Simplifying
-5x + -6(2x + -2) = -107

Reorder the terms:
-5x + -6(-2 + 2x) = -107
-5x + (-2 * -6 + 2x * -6) = -107
-5x + (12 + -12x) = -107

Reorder the terms:
12 + -5x + -12x = -107

Combine like terms: -5x + -12x = -17x
12 + -17x = -107

Solving
12 + -17x = -107

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -17x = -107 + -12

Combine like terms: 12 + -12 = 0
0 + -17x = -107 + -12
-17x = -107 + -12

Combine like terms: -107 + -12 = -119
-17x = -119

Divide each side by '-17'.
x = 7

Simplifying
x = 7

See similar equations:

| -8(3x+12)-13=4x+10 | | 2x+9=4(x+6) | | 15x+11x+20=90 | | 5x-10=-7x-70 | | y-19=6 | | 3x+6(2x-3)=102 | | x-5+8x=-1 | | -17/9= | | -6(10-7x)=-60 | | 15x+11x+20=180 | | -2=6x-2(x+19) | | 8x-2(7x+13)+9=5-4 | | -6(10-4f)=-3(-12+8f) | | (1.5x+20)+2x=90 | | 205=-7x-2(6x-17) | | -3/4w=-9 | | -6.5x=14.2 | | 8/9-8/9 | | t/5-7=10 | | 21=5x-4(x-7) | | 4x^2-48+108=0 | | x/6-1/5= | | x-4y=19fory | | 36=216n | | 3x+22=12x-15 | | -244=3x+7(-4x-17) | | 10(-5)= | | lnx=0.6 | | -1+4(2z-1)=3 | | 3x-70=260 | | 21x^2+192x+180=0 | | 12f-3f= |

Equations solver categories